OVERHEAD OPERATIONAL WATER FOOTPRINT DAN KUALITAS AIR PADA GEDUNG BERTINGKAT (STUDI KASUS GRAHA REKTORAT UNIVERSITAS NEGERI MALANG) - Anie Yulistyorini; Sanjaya Silvia; Dian Ariestadi (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2022)
Graha Rektorat Building at the State University of Malang (UM) significantly contributes to water usage. Water usage in the building must be managed and appropriately considered, so it can highly contribute to UM's ranking of UI Green Metric for water conservation indicators. Water usage can be calculated by analysis of overhead operational water footprint. This research aims to analyse green, blue, and grey water footprint, overhead operational water footprint, and the quality of green water on the Graha Rektorat building. The methods used in this research are the quantitative method. This research showed the blue water footprint, green water footprint, and grey water footprint of Graha Rektorat building each by 5628 m3 during January – September 2021, 4361.43 m3/year 18.575 m3/day. Overhead operational water footprint on Graha Rektorat building equal with the value of blue water footprint which is 5628 m3 during January – September 2021. The quality of green water on the Graha Rektorat building does not meet the requirements of Indonesian Minister of Health No. 32 of 2017 concerning environmental health quality standards and water health requirements for hygienic and sanitation purposes. Swimming Pools, Solus Per Aqua, and Public Baths, so as another alternative, green water can be used as a substitute for flushing toilets and watering plants to reduce blue water usage.